Transformation of Guidance and Counselling Programs in Vocational Schools: Integrated Evaluation Using the CIPP Model - Ayong Lianawati; Mochamad Nursalim; Retno Tri Hariastuti; Anita Dianasari; Ella Firda Mufidah (G-Couns: Jurnal Bimbingan dan Konseling, 2025)
Guidance and counselling programs support students' personal, social, and academic development. This study aims to determine the effectiveness of schools' personal and social guidance and counselling programs. This study uses the Context, Input, Process, Product (CIPP) model to evaluate vocational high schools' personal social guidance and counselling programs. The research method used is quantitative descriptive. Based on the results of the research that has been carried out related to the evaluation of the personal social guidance and counselling program at SMK Negeri 1 Kemlagi with the CIPP model, the results obtained indicate that the review of the personal social guidance and counselling program is in the good category. With these results, it is hoped that guidance and counselling teachers at SMK Negeri 1 Kemlagi can consistently continue improving services to maximise the results obtained per the expected goals. The evaluation results show an increase in the achievement of personal and social services by 41.89%, which is included in the outstanding category. All evaluation subcomponents, namely context, input, process, and product, are in the good to excellent categories. Keywords: evaluation program, guidance and counselling, CIPP model